2009
DOI: 10.1136/aim.2008.000174
|View full text |Cite
|
Sign up to set email alerts
|

Could Acupuncture Needle Sensation be a Predictor of Analgesic Response?

Abstract: During acupuncture some patients experience distinct sensations which are often referred to as needle sensation. Needle sensation may be related to treatment outcome, although what constitutes adequate acupuncture needle sensation is not known. In this paper, we debate the possibility of using the self-report of the overall intensity of needle sensation as a predictor of analgesic outcome to acupuncture. We describe how our approach to establish criteria to determine adequacy of transcutaneous electrical nerve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
21
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…In another study, greater analgesic effect (e.g., increased pressure pain threshold) was also reported in a treatment group with higher acupuncture needling sensation [6]. While several studies now suggest this link between needling sensation and clinical efficacy [7], other studies have not found associations between acupuncture sensations and analgesia [8], and controversy remains suggesting the need for more thorough research on this topic [9]. Acupuncture sensation may differ from evoked pain sensation, in terms of brain response, as suggested by neuroimaging studies [1013].…”
Section: Introductionmentioning
confidence: 99%
“…In another study, greater analgesic effect (e.g., increased pressure pain threshold) was also reported in a treatment group with higher acupuncture needling sensation [6]. While several studies now suggest this link between needling sensation and clinical efficacy [7], other studies have not found associations between acupuncture sensations and analgesia [8], and controversy remains suggesting the need for more thorough research on this topic [9]. Acupuncture sensation may differ from evoked pain sensation, in terms of brain response, as suggested by neuroimaging studies [1013].…”
Section: Introductionmentioning
confidence: 99%
“…7 It is claimed that acupuncture needle sensation may be an important determinant of acupunctureinduced pain relief yet surprisingly little research has been conducted to date. [8][9][10] Kong et al 5 conducted a pilot study on 11 healthy participants and found that reductions in experimental noxious thermal pain from manual and electroacupuncture were related to needle sensations of numbness and soreness but not stabbing, throbbing, tingling, burning, heaviness, fullness or aching. They used the Subjective Acupuncture Sensation Scale (SASS) to measure the self-report of needle sensation.…”
Section: Introductionmentioning
confidence: 99%
“…As such, the therapeutic effects of acupuncture may be seriously compromised. [12][13][14] In this study, we compared the efficacy of acupuncture with either strong (intended to elicit de qi) or weak stimulation among patients with Bell palsy. as susceptible to the psychosocial effect as analgesia is.…”
mentioning
confidence: 99%